Research output and sustainable development: webometric analysis of scopus indexed publications 2008 -2014 (2016)
The study evaluated research output indexed by Scopus between 2008 and 2014 in the month of April 2015. It assessed the quantity of research publication within the period, top ten published universities, fields, journals and their impact factors, cited authors, and top ten published countries. This was with a view to determining author relevance, institutional priority, the extent of sustainable development in the fields and host countries. Findings revealed that Li, Wei, of Harbin Institute of Technology China, Wang, Wei of Beijing University of Chemical Technology (BUCT) China, Zhang, Wei of Tsinghua University China, and Li, Hui Technische University Berlin, Germany were foremost among others during the period and their institutions and countries had more publications. Therefore, it is recommended that scholars, universities, and other institutions of higher learning especially in the developing nations should emulate these few to realize the yearnings of the world (sustainable global development).